Feminization of Higher Education in Poland in 1918-2018 - Popiński, Krzysztof (Studia Historiae Oeconomicae, 2019)
The text is devoted to women’s presence in the Polish higher education in 1918-2018. Its history is presented in chronological-thematic order, including information about the beginnings of women’s studies at universities as well as their basic political, economic and cultural conditioning. Although during the discussed period, basis of political system in Poland changed three times, there was a constant development of the size of higher education, as well as an increase of women’s participation among students and academic faculty. The beginnings were very modest. However, today women constitute already the majority of students of higher education and almost a half of academic employees. Women, during their fight for equality in access to studies and academic career, had to overcome many legal obstacles, also informal ones, resulting from vitality of the image of traditional social role of women. Even though, the formal equality was gradually earned, it is still more difficult for women than for men to undertake studies at some faculties, and to get higher degrees and academic positions as fast as men.